Tornando-se professor de instrumento: narrativas de docentes-bacharéis - Weber, Vanessa (2014)
This dissertation relates to the Research Field of Education and Arts LP4, at the Education Graduate Department of Universidade Federal de Santa Maria (PPGE/UFSM) and to the study group Education, Action and Research in Music Education (FAPEM). The general objective was to understand the Bachelor in instrument s process of learning to teach musical instruments. In particular, we tried to understand their education process and to investigate the knowledge that these teachers mobilize when teaching their instrument. This research had a qualitative approach and adopted as its methodology the biographic-narrative investigation (BOLÍVAR, DOMINGO, 2006), through which the narratives of three bachelors who teach instruments were produced. By means of textual discursive analysis (MORAES; GALIAZZI, 2013), data analysis categories were created, which were interpreted based on the adopted theoretical framework. In this sense, the production of the text about the learning to teach and about the mobilized knowledge was based on studies by Bolzan (2002), Bolzan and Isaia (2006), Isaia and Bolzan (2009, 2010), Gauthier et al. (2006) e Tardif (2012). While we are aware that the three collaborator s narratives do not represent the totality of the educational path for teaching, we conclude that each bachelor in instrument becomes a teacher-bachelor through the construction and mobilization of knowledge, which are integrated to the being a teacher through education and experience with pedagogical practice. Furthermore, besides the knowledge described by Gauthier et al. (2006) an Tardif (2012), we identified the performance knowledge, which is specific of the instrument teacher.